Calcimimetic Drugs and Biomarkers - Rothe, Hansjorg; Liangos, Orfeas; Petermann, Arndt; Biggar, Patrick; Ketteler, Markus (Recent Patents on Biomarkers, 2014)
The calcium-sensing receptor is expressed almost ubiquitously throughout the human body, and is essential for calcium homeostasis and is involved in several disease pathomechanisms. Mainly in nephrology, therapeutic compounds acting on the receptor are already in use in clinical routine practice. The era of calcimimetic therapy, which commenced 10 years ago with the approval of the first-in-class compound cinacalcet HCl, has recently entered into a new phase with the arrival of velcalcetide (AMG416). Since both compounds bind to different sites at the receptor molecule, genetic polymorphism panels could conceivably play a role in future for the prediction of the best choice for any given patient. If velcalcetide, which has currently just passed phase-III-trials, is also approved for therapeutic use, this will increase the spectrum of choices and the clinician will have to make decisions about which calcimimetic drug to give to which patient. This decision would probably have to be based on various considerations including biomarkers. This article summarizes the present situation regarding patents on biomarkers dealing with the calcium-sensing receptor and genetic polymorphisms.
Keywords: calcium-sensing receptor